The Effectiveness of Scientific Approach in Teaching Procedure Text Using Video to Improve Speaking Skill for Grade 9 Students of SMPN 32 Semarang - Ananda Latifah Azhar Rachma Nabila; Dyah Nugrahani; Ririn Ambarini (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The study was conducted to determine the effectiveness of scientific approach and video media to improve students’ speaking skill. The aim was to find out significant differences between the experimental class that received treatment and the control class that did not receive treatment. The research was conducted for 4 days at SMPN 32 Semarang with a population of all ninth grade students. Meanwhile, the samples were from IXF as the experimental class and IXG as the control class. There are 30 students in each class who participated. The research is quantitative research and used quasi-experimental method. Instrument of the study was oral test and collected the data used pre-test and post-test. Technique of data analysis used IMB SPSS version 25. After 4 days of treatment, the average student learning outcomes were very significant. The Mean score of control class is 63.2 and experimental class is 80.9. The average score of the control class is lower than the experimental class, which means that te control class showed a slight improvement after the learning process without using a scientific approach and video media. Meanwhile, the experimental class showed significant improvement after the learning process using a scientific approach and video media. The results have been processed through SPSS and produced significant differences between the control class and the experimental class. So, it can be conclude that a scientific approach and video media are effective to improve students’ speaking skill.